2012
DOI: 10.1002/hyp.8400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rainfall on soil moisture and water movement in a subalpine dark coniferous forest in southwestern China

Abstract: Abstract:Water content and movement in soil profile and hydrogen isotope composition (dD) of soil water, rainwater, and groundwater were examined in a subalpine dark coniferous forest in the Wolong National Nature Reserve in Sichuan, China, following rainfall events in [2003][2004]. Light rainfall increased water content in the litter and at soil depth of 0-80 cm, but the increased soil water was lost in several days. Heavy rainfall increased soil water content up to 85% at depths of 0-40 cm. Following the lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 25 publications
5
25
0
Order By: Relevance
“…Their results clearly showed that light rainfall (5-15 mm) events only temporally altered the shape of δD profile curve of soil water, and their impacts on the upper soil depth were quickly depleted through evaporation and plant uptake. In contrast, heavy rainfall events (about 30 mm) greatly affected the shape of δD profile curve of soil water in all layers (Xu et al, 2011a). Surprisingly, groundwater in shallow aquifers was not significantly altered at this heavy rainfall intensity.…”
Section: Impacts Of Forest Changes On Water At a Forest Stand Levelmentioning
confidence: 72%
See 1 more Smart Citation
“…Their results clearly showed that light rainfall (5-15 mm) events only temporally altered the shape of δD profile curve of soil water, and their impacts on the upper soil depth were quickly depleted through evaporation and plant uptake. In contrast, heavy rainfall events (about 30 mm) greatly affected the shape of δD profile curve of soil water in all layers (Xu et al, 2011a). Surprisingly, groundwater in shallow aquifers was not significantly altered at this heavy rainfall intensity.…”
Section: Impacts Of Forest Changes On Water At a Forest Stand Levelmentioning
confidence: 72%
“…Using the isotopic method, Xu et al (2011a) analyzed the responses of δD to different rainfall intensities in different soil layers (litter, humus, illuvial, mineral soil and shallow aquifer) in a subalpine, dark coniferous forest in the Wolong Natural Nature Reserve of the study watershed. They found that different soil layers had different responses (change rates and lengths of residence time) to rainfall intensities and subsequent evapotranspiration, with quick responses in top layers and slow responses in deep layers.…”
Section: Impacts Of Forest Changes On Water At a Forest Stand Levelmentioning
confidence: 99%
“…At 20 the 75 th percentile all drought index values below zero were taken as drought events. Together with the pF 5 and pF 30 thresholds, this defines the segments a, b and c used in equation (3) and (4) and illustrated in Appendix B. However the FR and the FAR will be same when we use same threshold of both drought index and soil water pressure (in this study 75 th percentile), because the a and c values in equation (3) and (4) will be same.…”
Section: Step 3 Evaluation Of the Drought Indices Against Minimum Somentioning
confidence: 99%
“…We also evaluated the correlations between pF 5 and pF 30 and 5 SPI i-1 and RDI i-1 in case the three month averages defined in equation (1) and (2) more strongly influence the next month's minimum soil water pressure.…”
Section: Step 3 Evaluation Of the Drought Indices Against Minimum Somentioning
confidence: 99%
See 1 more Smart Citation